(untitled) (Journal of Philosophy Culture and Political Science, 2018)
The article analyzes the plays of the last century, discusses spiritual values and the historical importance of the ideas inherent to them. Despite the low level of works of the founders of the national drama such as K. Togusov, A.I. Likhanov, B. Serkebayev and others, the article stresses the value of these works as plays of the initiators of the Kazakh dramatic art. Having carried out a scientific analysis of the play «Khan Kene» by M.Auezov, «Amankeldi» by G. Musrepov, «Issatay – Makhambet», «Revenge» by I. Zhansugurov, «Issatay – Makhambet» by M. Ahinzhanov, «Makhambet» by G. Slanov, «Wounded Tiger» by K. Myrzaliyev, «Makhambet» by Iran-Gaiyp, the authors demonstrate the causes of the development of the national liberation movement. Not overlooked by the authors of the article is the search for socio-historical images of famous historical figures such as Kenesary, Isatay, Makhambet, Zhangir, Baimagambet carried out by the playwrights. Along with this, accurate historical facts are outlined in revealing the character of the heroes of the analyzed works, their political views on the future of revolution. Words and actions, the idea and the related physical connections in the stage directions of the playwrights are confirmed by scientific conclusions. Key words: national drama, theatre, art, history, conception, literary genre, writer, independence, revolution, dialogue, search, social position.